QURANIC INTERPRETATION BY OPINION MEANING, TYPES ANALYTICAL STUDY - Reeda Mushtaq; Dr Abdul Rehman; Sitara Jabeen (Journal of Religion and Society, 2025)
This paper presents an in-depth analysis of "Tafseer Bil Ra’y" (interpretation of the Quran based on personal opinion), exploring its meaning, legitimacy, and various forms. It delves into the principles and conditions required for its valid application, emphasizing the limitations within which scholars have permitted its use. The significance of this topic lies in its ability to offer a more expansive understanding of Quranic verses, especially in addressing contemporary issues. The research aims to clarify the concept of Tafseer Bil Ra’y, analyze its different forms, and examine its role in modern times. Furthermore, the study investigates the impact of personal judgment in Quranic exegesis and its ongoing relevance in Islamic scholarship. The paper also explores how the application of personal judgment can be used responsibly to address current challenges while maintaining the integrity of the Quranic message. Recommendations for further research include a deeper examination of the principles and criteria for valid Tafseer Bil Ra’y, a more detailed analysis of its different forms and their implications, and an exploration of its application to contemporary issues, including those in modern social, scientific, and ethical contexts. This study contributes to the ongoing discourse on the interpretation of the Quran and its application in today’s world. Keywords: Quranic Interpretation Methodologies, Scholarly Views on Opinion-Based vs Traditional Tafsir, Principles of Quranic Exegesis